ANALISIS PERJANJIAN PEMBELIAN APARTEMEN T. PLAZA DENGAN SISTEM PRE PROJECT SELLING DITINJAU DARI PERATURAN MENTERI PEKERJAAN UMUM DAN PERUMAHAN RAKYAT NOMOR 11/PRT/M/2019 TENTANG SISTEM PERJANJIAN PENDAHULUAN JUAL BELI RUMAH (STUDI KASUS: PUTUSAN PENGADILAN NEGERI JAKARTA PUSAT NOMOR 145/PDT.G/2019) - Melvina Melvina; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2021)
Buying and selling transactions of either a unit of apartment or a house in Indonesia, the transaction records by pre-project selling agreements that deviate from the provisions of Article 1 Paragraph (2) jo. Article 9 Paragraphs (1) and (2) jo. Article 10 Paragraph (1) Regulation of the Minister of Public Works and Human Settlement Number 11/Prt/M/2019 concerning the Preliminary Agreement System for the Sale and Purchase of Houses (Permen PUPR PPJB). The use of the pre project selling agreement greatly weakens the legal position of the apartment buyer/consumer due to the use of standard clauses, the unclear legal status of the buyer of the T. Plaza apartment unit which is not made by PPJB before a notary, all payments made by the buyer are not returned and prior to marketing the apartment construction. T. Plaza has not yet reached 20% of the building construction volume. All of the above issues will be discussed in this article through the study of Decision Number 145/Pdt.G/2019/PN Jkt.Pst. In this decision, the sale and purchase of apartments is carried out through a letter of order number 353/PK-TP/X/2013. The first problem is how is the legal force of the order letter number 353/PKTP/X/2013 in terms of the Regulation of the Minister of Public Works and Public Housing Number 11/PRT/M/2019 concerning the Preliminary Agreement System for the Sale and Purchase of Houses? and secondly, what are the legal considerations of judex fact in the civil case decision number 145/Pdt.G/2019/PN Jkt.Pst, when it says the buyer is in default?. This research was conducted using normative legal research methods. The results of the study show that the rise of apartment unit transactions using pre-project selling without a notarial deed is made, thus weakening the position of buyers with good intentions.